Determination of Lawsone by HPTLC in Lawsonia inermis L. Callus and Plantlets Regenerated in vitro - S. Phirke, Snehal; Saha, Moitreyee (Asian Journal of Chemistry, 2014)
Leaves of Lawsonia inermis L. (henna) contain lawsone (2-hydroxy-1, 4-naphthaquinone). The orange red dye is used for colouring hair and hands. Lawsone also exhibits antifungal, antibacterial and antioxidant activity. HPTLC technique was used for estimation of lawsone in Lawsonia inermis L. plantlets regenerated in vitro and callus derived from leaf explants of in vitro seedlings. The content of lawsone found was 0.057 μg/mg in plantlet regenerated in vitro and 0.017 μg/mg (callus powder) of Lawsonia inermis L.